2022
DOI: 10.1002/asia.202200587
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Carbonyl Chemistry in Non‐aqueous Mg Flow Batteries

Abstract: Non-aqueous redox flow batteries (RFBs) are emerging electrochemical technologies for grid energy storage. Non-aqueous Mg RFBs that use Mg metal as the anode are especially promising due to various benefits of the Mg metal anode, including its low potential, high volumetric capacity, SEI-free, highly reversible operation and low cost. Despite the potential, there are rarely any studies on developing non-aqueous Mg RFBs. Herein, a non-aqueous Mg redox flow battery using a polymer catholyte is reported. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…71–75 Since 2019, Luo et al have reported various linear and porous polymers as cathode materials for alkali-ion and multivalent metal batteries. 76–81 The results illustrate that developing organic salts and high-molecular-weight polymers can effectively overcome the high solubility challenge of organic batteries. Extended conjugation structures in OEMs enhance reaction kinetics and enable fast charging capability.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…71–75 Since 2019, Luo et al have reported various linear and porous polymers as cathode materials for alkali-ion and multivalent metal batteries. 76–81 The results illustrate that developing organic salts and high-molecular-weight polymers can effectively overcome the high solubility challenge of organic batteries. Extended conjugation structures in OEMs enhance reaction kinetics and enable fast charging capability.…”
Section: Introductionmentioning
confidence: 95%
“…11a). 80,81 The polyimides were used as catholyte materials to couple with a Mg metal anode. Here, redox-active polymers rather than small organic molecules are used as catholyte materials in flow batteries because the large size of the polymers can mitigate the crossover of active materials through the membrane, which is a major challenge in redox-flow batteries.…”
Section: Organic Batteriesmentioning
confidence: 99%